Bas Relief at Construction House - Ghosh, Ayan (2023)
Hindustan Construction Company had leased the plot from the Bombay Port Trust for 99 years. For Construction House, they commissioned Messrs. Gregson, Batley & King, who had designed several notable Art Deco buildings in Mumbai, like Dhanraj Mahal, Windsor House, Cricket Club of India, and Breach Candy Hospital, among others.